The Role of the Sustainable Development Concept in Shaping Energy Policy Transformations in the Caspian Region Countries - R. A. Aliev (Vestnik MGIMO-Universiteta)
The article explores the challenges associated with the adaptation of energy policies in the Caspian region to the principles of sustainable development. In the contemporary context, the oil and gas resources of Caspian countries play a vital role in national economic development and ensuring energy security for key importing nations amidst the global reshuffling of energy flows. The author analyzes the transformative changes brought about by the energy transition within the structure of the global fuel and energy complex.The study contributes to the field by proposing an integrated approach to promoting energy sustainability in energy-exporting countries. This approach entails the adaptation of the oil and gas sector to decarbonization processes, while simultaneously embracing the development of carbon-free energy sources within a dynamically evolving geopolitical landscape. The research endeavor seeks to determine the main directions for transforming the energy policies of oil and gas producing countries in the Caspian region in response to imperatives of sustainable development.At present, the most relevant aspects of energy policy in the Caspian countries involve the further development of oil and gas projects, strict adherence to environmental standards and regulations, ensuring energy efficiency across the entire production chain, and the implementation of "operational decarbonization" measures and carbon capture and storage technologies to reduce the carbon footprint of the fuel and energy complex. Additionally, to mitigate climate risks in the Caspian region, strategic energy policy priorities should encompass resource diversification towards the advancement of carbon-free generation based on renewable energy sources.The study assesses the potential of the Caspian countries not only in implementing "operational decarbonization" measures but also in developing renewable and low-carbon energy sources. Furthermore, it examines the prospects for realizing ambitious "green" projects in the region.